Economic transition and urban transformation of China: The interplay of the state and the market. (November 2015) - Yeh, Anthony GO; Yang, Fiona F; Wang, Jiejing
The transition of the Chinese economy from plan to market has led to dramatic economic restructuring and urban transformation since the economic reforms and open door policy in 1978. The state and the market, which are the two basic regulating mechanisms, have significantly changed their role in economic and urban development in this transition in China. We attempt to examine the interplay of the state and the market in facilitating economic growth and producing 'new' urban space after replacing socialism with state capitalism. Four major waves of urbanisation and urban development have been identified, in terms of the interaction of the state and the market in producing different forms of urban development which also bring about economic transition in China. We further examine the new form of urban development in the fourth stage of urbanisation which is represented by the rapid growth of producer services and the resulting development of central business districts. Economic transition and urban transformation in China seem to converge with the development pattern of developed and other developing countries. However, embedded in a different state–market interplay, the experience of Chinese cities may be different and not be easily imitated by cities in other developing countries.